2021
DOI: 10.1002/mar.21620
|View full text |Cite
|
Sign up to set email alerts
|

The effects of packaging design of private brands on consumers' responses

Abstract: This study examines how retailers can capitalize on the packaging design for multitier private brands to drive positive consumer responses. We shed light on cognitive and affective consumer responses in relation to consumers' visual processing, price‐consciousness, and perception of retailer‐private brand congruity. The results of two studies, a pilot test, and a post‐hoc test with US consumers confirm that premium packaging design has a strong, positive impact on brand equity and consumer choice of private br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 90 publications
1
9
0
1
Order By: Relevance
“…Known as the price‐quality heuristic , it is one of the core findings in traditional‐marketing literature (Chang & Wildt, 1996; Chitturi et al, 2010; Kardes et al, 2004; Woodside, 2012) and has been shown to apply across a wide range of situations where people report their beliefs and preferences for products (John et al, 1986; Lalwani & Monroe, 2005; Naylor et al, 2006; Niemand et al, 2019; Pechmann & Ratneshwar, 1992; Rao, 2005; Rao & Monroe, 1988; Suri & Monroe, 2003; Veale & Quester, 2009; Verdú Jover et al, 2004). It also corroborates prior work showing that consumers rely on external product attributes to gauge product quality (Allison & Uhl, 1964; Garvey et al, 2016; Gonçalves et al, 2020; Hwang & Kim, 2022; Marozzo et al, 2020; Moore & Olshavsky, 1989; Rauschendorfer et al, 2022; Solja et al, 2018)—particularly when quality information is difficult to access (Akdeniz et al, 2013). Thus, telling a person that something costs more will elicit expectations of better quality and liking.…”
Section: Introductionsupporting
confidence: 85%
“…Known as the price‐quality heuristic , it is one of the core findings in traditional‐marketing literature (Chang & Wildt, 1996; Chitturi et al, 2010; Kardes et al, 2004; Woodside, 2012) and has been shown to apply across a wide range of situations where people report their beliefs and preferences for products (John et al, 1986; Lalwani & Monroe, 2005; Naylor et al, 2006; Niemand et al, 2019; Pechmann & Ratneshwar, 1992; Rao, 2005; Rao & Monroe, 1988; Suri & Monroe, 2003; Veale & Quester, 2009; Verdú Jover et al, 2004). It also corroborates prior work showing that consumers rely on external product attributes to gauge product quality (Allison & Uhl, 1964; Garvey et al, 2016; Gonçalves et al, 2020; Hwang & Kim, 2022; Marozzo et al, 2020; Moore & Olshavsky, 1989; Rauschendorfer et al, 2022; Solja et al, 2018)—particularly when quality information is difficult to access (Akdeniz et al, 2013). Thus, telling a person that something costs more will elicit expectations of better quality and liking.…”
Section: Introductionsupporting
confidence: 85%
“…It is completely consumer-centered and refuses mandatory information input. People have the right to choose information [5]. The application of AR technology can reduce unnecessary text information on packaging and decoration, effectively enhancing the overall artistic beauty of the packaging, while the information is hidden in the AR virtual scene, which is a new interactive form brought by technology to people, completely independent.…”
Section: Introductionmentioning
confidence: 99%
“…According to the cue utilization theory (Olson, 1978), products/packaging present multiple cues, which consumers use to assess the products. These cues are acquired and processed to determine purchasing decisions (Hwang & Kim, 2022)…”
Section: Vr and Product Researchmentioning
confidence: 99%
“…According to the cue utilization theory (Olson, 1978), products/packaging present multiple cues, which consumers use to assess the products. These cues are acquired and processed to determine purchasing decisions (Hwang & Kim, 2022). Since VR can replicate RL elements and deliver realistic cues, it would seem reasonable to achieve similar results across the two realities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%